Strategie komunikacyjne Marcina Pabierowskiego w kampanii wyborczej na urząd Prezydenta Miasta Zielona Góra w 2024 r. - Polak-Woźniak, Alina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the communication strategies employed by Marcin Pabierowski during his 2024 mayoral campaign in Zielona Góra. The study draws on key concepts from political marketing theory, particularly the 4P and 7P marketing-mix models and B.I. Newman`s image component framework. The author focuses on direct voter engagement, the use of new media, positive narrative construction, endorsement from political figures, and the symbolic and emotional dimensions of the candidate`s image. The analysis demonstrates that Pabierowski`s victory resulted from a consistent combination of image-building efforts with authentic citizen interaction and effective local-level communication management. This case study confirms the increasing importance of relationship marketing in contemporary local election campaigns.
Keywords: marketing polityczny; kampania wyborcza; komunikacja polityczna; wizerunek kandydata; Pabierowski, Marcin (1978- ); Zielona Góra (okręg); political marketing; election campaign; political communication; candidate image